Obicetrapib exhibits favorable physiochemical and pharmacokinetic properties compared to previous cholesteryl ester transfer protein inhibitors: An integrated summary of results from non‐human primate studies and clinical trials - Stephen J. Nicholls; Adam J. Nelson; John J. P. Kastelein; Marc Ditmarsch; Andrew Hsieh; Judith Johnson; Danielle Curcio; Douglas Kling; Carol F. Kirkpatrick; Michael H. Davidson (Pharmacology Research & Perspectives)
Abstract Anacetrapib, a cholesteryl ester transfer protein (CETP) inhibitor previously under development, exhibited an usually extended terminal half‐life and large food effect and accumulated in adipose tissue. Other CETP inhibitors have not shown such effects. Obicetrapib, a potent selective CETP inhibitor, is undergoing Phase III clinical development. Dedicated assessments were conducted in pre‐clinical and Phase I and II clinical studies of obicetrapib to examine the pharmacokinetic issues observed with anacetrapib. After 9 months of dosing up to 50 mg/kg/day in cynomolgus monkeys, obicetrapib was completely eliminated from systemic circulation and not detected in adipose tissue after a 13‐week recovery period. In healthy humans receiving 1–25 mg of obicetrapib, the mean terminal half‐life of obicetrapib was 148, 131, and 121 h at 5, 10, and 25 mg, respectively, and food increased plasma levels by ~1.6‐fold with a 10 mg dose. At the end of treatment in Phase II trials, mean plasma levels of obicetrapib ranged from 194.5 ng/mL with 2.5 mg to 506.3 ng/mL with 10 mg. Plasma levels of obicetrapib decreased by 92.2% and 98.5% at four and 15 weeks post‐treatment, respectively. Obicetrapib shows no clinically relevant accumulation, is minimally affected by food, and has a mean terminal half‐life of 131 h for the 10 mg dose. These data support once daily, chronic dosing of obicetrapib in Phase III trials for dyslipidemia management.